Assessment of EnMAP data quality through global product validation activities - Maximilian Brell; Philipp Reiners; Luis Guanter; Karl Segl; Sabine Chabrillat; Daniel Scheffler; Mariana A. Soppa; Niklas Bohn; Javier Gorrono; Alexander Kokhanovsky; Astrid Bracher; Martin Bachmann; et al. (Remote Sensing of Environment, 2026)

The EnMAP spaceborne imaging spectroscopy mission: Initial scientific results two years after launch - Sabine Chabrillat; Saskia Foerster; Karl Segl; Alison Beamish; Maximilian Brell; Saeid Asadzadeh; Robert Milewski; Kathrin J. Ward; Arlena Brosinsky; Katrin Koch; Daniel Scheffler; Stephane Guillaso; et al. (Remote Sensing of Environment, 2024)

The EnMAP imaging spectroscopy mission towards operations - Tobias Storch; Hans-Peter Honold; Sabine Chabrillat; Martin Habermeyer; Paul Tucker; Maximilian Brell; Andreas Ohndorf; Katrin Wirth; Matthias Betz; Michael Kuchler; Helmut Mühle; Emiliano Carmona; et al. (Remote Sensing of Environment, 2023)

LRP2 contributes to planar cell polarity-dependent coordination of motile cilia function - Lena Bunatyan; Anca Margineanu; Camille Boutin; Mireille Montcouquiol; Sebastian Bachmann; Erik Ilsø Christensen; Thomas E. Willnow; Annabel Christ (Cell and Tissue Research, 2023)
Motile cilia are protruding organelles on specialized epithelia that beat in a synchronous fashion to propel extracellular fluids. Coordination and orientation of cilia beating on individual cells and across tissues is a complex process dependent on planar cell polarity (PCP) signaling. Asymmetric sorting of PCP pathway components, essential to establish planar polarity, involves trafficking along the endocytic path, but the underlying regulatory processes remain incompletely understood. Here, we identified the endocytic receptor LRP2 as regulator of PCP component trafficking in ependyma, a multi-ciliated cell type that is involved in facilitating flow of the cerebrospinal fluid in the brain ventricular system. Lack of receptor expression in gene-targeted mice results in a failure to sort PCP core proteins to the anterior or posterior cell side and, consequently, in the inability to coordinate cilia arrangement and to aligned beating (loss of rotational and translational polarity). LRP2 deficiency coincides with a failure to sort NHERF1, a cytoplasmic LRP2 adaptor to the anterior cell side. As NHERF1 is essential to translocate PCP core protein Vangl2 to the plasma membrane, these data suggest a molecular mechanism whereby LRP2 interacts with PCP components through NHERF1 to control their asymmetric sorting along the endocytic path. Taken together, our findings identified the endocytic receptor LRP2 as a novel regulator of endosomal trafficking of PCP proteins, ensuring their asymmetric partition and establishment of translational and rotational planar cell polarity in the ependyma.

A Density-Dependent Target Stimulus for Inverse Bone (Re)modeling with Homogenized Finite Element Models - Sebastian Bachmann; Dieter H. Pahr; Alexander Synek (Annals of Biomedical Engineering, 2023)
Inverse bone (re)modeling (IBR) can infer physiological loading conditions from the bone microstructure. IBR scales unit loads, imposed on finite element (FE) models of a bone, such that the trabecular microstructure is homogeneously loaded and the difference to a target stimulus is minimized. Micro-FE (µFE) analyses are typically used to model the microstructure, but computationally more efficient, homogenized FE (hFE) models, where the microstructure is replaced by an equivalent continuum, could be used instead. However, also the target stimulus has to be translated from the tissue to the continuum level. In this study, a new continuum-level target stimulus relating relative bone density and strain energy density is proposed. It was applied using different types of hFE models to predict the physiological loading of 21 distal radii sections, which was subsequently compared to µFE-based IBR. The hFE models were able to correctly identify the dominant load direction and showed a high correlation of the predicted forces, but mean magnitude errors ranged from − 14.7 to 26.6% even for the best models. While µFE-based IBR can still be regarded as a gold standard, hFE-based IBR enables faster predictions, the usage of more sophisticated boundary conditions, and the usage of clinical images.

From tubular sublimate nephropathy via urinary concentrating mechanism to glomerular disease—Wilhelm Kriz’s contribution to modern nephrology - Sebastian Bachmann (Pflügers Archiv - European Journal of Physiology, 2017)

Regulation of renal Na-(K)-Cl cotransporters by vasopressin - Sebastian Bachmann; Kerim Mutig (Pflügers Archiv - European Journal of Physiology, 2017)

Localization of the iron-regulatory proteins hemojuvelin and transferrin receptor 2 to the basolateral membrane domain of hepatocytes - Uta Merle; Franziska Theilig; Evelyn Fein; Sven Gehrke; Birgit Kallinowski; Hans-Dieter Riedel; Sebastian Bachmann; Wolfgang Stremmel; Hasan Kulaksiz (Histochemistry and Cell Biology, 2007)

Renal and endocrine changes in rats with inherited stress-induced arterial hypertension (ISIAH) - Sergej Amstislavsky; Pia Welker; Jan-Henning Frühauf; Larissa Maslova; Ludmila Ivanova; Boye Jensen; Arkady L. Markel; Sebastian Bachmann (Histochemistry and Cell Biology, 2006)

Selectively reduced expression of thick ascending limb Tamm-Horsfall protein in hypothyroid kidneys - Roland Schmitt; Thomas Kahl; Kerim Mutig; Sebastian Bachmann (Histochemistry and Cell Biology, 2004)

Sedimentary response to basin inversion: Mid cretaceous-early tertiary pre- to syndeformational deposition at the Areif El Naqa anticline (Sinai, Egypt) - Sebastian Lüning; Jochen Kuss; Martina Bachmann; Ahmed M. Marzouk; Ahmed M. Morsi (Facies, 1998)